POLITENESS STRATEGY ANALYSIS ON THE TONIGHT SHOW STARRING JIMMY FALLON - Adela Yusniati; Marwito Wihadi; Wulan Rahmatunisa (Journey: Journal of English Language and Pedagogy, 2023)
The purpose of this study is to identify the politeness strategies used by Taylor Swift and Paul Rudd in the Tonight Show with Jimmy Fallon YouTube videos "Taylor Swift Talk RecordBreaking Midnight Album, Music Video Cameos and Easter Eggs" and "Paul Rudd Compares His Men's Health Shoot with Jonathan Majors' (Extended)" when they decide to use particular politeness strategies in communication. The research employed a qualitative descriptive method using an observational data collecting technique is applied to analyze the speakers' manner politeness strategies affect the communication between the speaker and hearer. Data collected from observation were analyzed using discourse analysis interpretation and were classified regarding the Brown and Levinson (1987) theory. This research found that the speakers both of Taylor and Paul prevalence the positive politeness strategy when they communicating in Jimmy Fallon’s show. the positive politeness strategy that appeared in Taylor Swift that she is usually showing exaggerate (interest approval, sympathy with Hearer) while Paul Rudd deals with his character who really like making a joke almost in the whole conversation. Besides, the differences also followed by the second strategies that revealed by Taylor and Paul. Taylor Swift commonly chosen negative politeness strategy and Paul Rudd deals with off-record politeness strategy